Current trends in theranostic applications of extracellular vesicles in cancer - Almasry, Yazan; Mustafa, Fayrouz; Alfuwais, Mohammed; AlNachef, Sara; Mohamed, Hager; Gaber, Nusaibah S.; Khan, Mohammed Imran; Saadeldin, Islam M.; Yaqinuddin, Ahmed (Frontiers in Oncology, 2025)
BackgroundExtracellular vesicles (EVs) play an integral role in cancer biology, influencing tumor progression, metastasis, and tumor microenvironment. Due to their distinctive molecular composition, including proteins, nucleic acids, and lipids, EVs present a promising candidate for cancer diagnostics and precision therapeutics.MethodsThis review was conducted by looking up recent studies obtained through PubMed, Scopus, and Web of Science databases using targeted keywords such as “Extracellular Vesicles,” “Cancer Therapy,” “Biomarkers,” “Exosomes,” “Tumor Microenvironment,” and “Precision Medicine.” From an initial 4,320 articles identified, 427 were screened after applying publication filters, resulting in the inclusion of 298 articles relevant to EV isolation, characterization, diagnostic sensitivity, specificity, and therapeutic efficacy.ResultsBiomarkers derived from EVs derived across various cancers showed high diagnostic performance. For example, four miRNA EVs showing sensitivity and specificity of 98% and 96% respectively was found in breast cancer. EV-RNA and surface antigen analyses for hepatocellular carcinoma with 93.8% sensitivity and 74.5% specificity. Additionally, EV biomarker cancers of the colorectal microRNA miR-23a and miR-301a had 89% sensitivity and >70% specificity. EVs in a therapeutic context were an effective drug delivery system for enhancing precision of chemotherapy and immunotherapy with reduced systemic toxicity.ConclusionThe theranostics of EVs provide great capacity for early cancer diagnosis and personalized treatment based on their high diagnostic sensitivity and specificity. Future standardization protocols are essential to translate EV technologies into clinical oncology.